Characteristics of confined exciton states in silicon quantum wires - Korbutyak, D.V.; Kryuchenko, Yu.V.; Kupchak, I.M.; Sachenko, A.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2003)
We have studied theoretically the combined effect of quantum confinement and "dielectric enhancement" on the characteristics of the exciton ground state in quasi-1D silicon nanowires. Consideration has been made within effective mass and classical image force approximations. As a result, exciton binding energy, total energy of the exciton transition, radiative recombination time, intensity and internal quantum efficiency of the exciton photoluminescence (PL) in quantum wires (QW) have been obtained as functions of wire thickness, dielectric constants of adjacent materials, conduction and valence band-offsets. It was shown that even at room temperatures and moderate intensities of laser excitation the quantum efficiency of the exciton PL can achieve very high values (tens of %) in the case of extremely thin QWs (with thickness 1 - 3 nm). Moreover, according to theory, the exciton recombination time and the quantum efficiency have to be oscillating functions of QW thickness in thickness range 1 - 5 nm due to the indirect band-gap nature of silicon material.